Efektifitas senam aerobic low impact terhadap Aggression self control pada pasien dengan Resiko perilaku kekerasan - Nadzla - Kirana; Fathra Annis Nauli; Riri - Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The research aimed to analize the effectiveness oflow impact aerobic exercise toward aggression self control in patients with risk of violence behaviour. The research applied quasy experiment studywithpretest-posttest design with control group. The research was conducted in psychiatric hospital Tampan Riau Province with sample of 34 patients withrisk of violence behaviour which divided into 17 people as experimental group and 17 people as control group and choosen by purposive sampling method. Instruments of this research usedaggression self control questionnaire which has tested the validity and reliability for both of groups. Experimental group is trained with low impact aerobic exercise for three times a week for 2 weeks, meanwhile control group were not. Paired t-test and t-test statistical analysis were used to analyze the data. The result of the research showed that mean aggression self control scoreposttest in experimental group was 45,76 and control group was 21,94. That means, there was an increasing number of aggression self control after intervention in experimental group with p value= 0,000 (p<0,05). This study revealed that low impact aerobic exercise could increased aggression self control in patients with risk of violence behaviour. The result of this research recommended to be applied for nursing intervention to increase aggression self control in patients with risk of violence behaviour. Keywords: Aggression self control,low impact aerobic exercises, violence behaviour.